Surviving the final year project (FYP) presentation during the pandemic: students' satisfaction with the video presentation mode - Nurul Hidayana Mohd Noor, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The COVID-19 pandemic significantly impacted the Malaysian economy and adversely affected several critical sectors, including the market, retail, hospitality, tourism, and education. The effects of the COVID-19 pandemic on the education sector caused the government to implement an online learning program. Online learning is considered the most effective and efficient way to learn amid the current pandemic and during the post-pandemic. Employing a quantitate survey study, this study aims to explore the enablers that support students engaging in a video presentation. A total of 181 final-year students from the Faculty of Administrative Science and Policy Studies, Universiti Teknologi MARA (UiTM), were selected as informants. This study examines the influence of reduction in comparison bias, group participation, product originality, product demonstrability, perceived usefulness, and perceived enjoyment on student satisfaction with video presentations. A valid of 175 respondents' data were analysed using descriptive analysis, Pearson correlation, and multiple regression. Pearson's correlation analysis found significant relationships between all determinants and student satisfaction with video presentations. Analysis of multiple regression techniques shows that perceived enjoyment predicts student satisfaction with video presentations. The faculty and university management can use the results of this study to plan and draft structured programs to improve student technological skills and performance. Lecturers also can provide appropriate teaching methods and tools to assist students in using and developing their final year project (FYP) presentation.